2007
DOI: 10.1371/journal.pone.0001148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Flaxseed-Derived Lignan Supplement in Type 2 Diabetic Patients: A Randomized, Double-Blind, Cross-Over Trial

Abstract: BackgroundFlaxseed consumption has been shown to improve blood lipids in humans and flaxseed-derived lignan has been shown to enhance glycemic control in animals. The study aimed to investigate the effect of a flaxseed-derived lignan supplement on glycemic control, lipid profiles and insulin sensitivity in type 2 diabetic patients.Methodology/Principal FindingsThis was a randomized, double-blind, placebo-controlled, cross-over trial and it was conducted between April and December 2006 in Shanghai, China. Seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
120
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(153 citation statements)
references
References 36 publications
8
120
0
3
Order By: Relevance
“…The present work is based on recent epidemiological and experimental evidences, suggesting that lignan-rich foods, such as oilseeds, may improve metabolic functions underlying metabolic syndrome (MetS) [17,22,29,[32][33][34]. The focus was directed to study two of the most lignan-rich food sources: sesame and flaxseeds, which contain up to 1 % lignans (500-1,000 mg/100 g) [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The present work is based on recent epidemiological and experimental evidences, suggesting that lignan-rich foods, such as oilseeds, may improve metabolic functions underlying metabolic syndrome (MetS) [17,22,29,[32][33][34]. The focus was directed to study two of the most lignan-rich food sources: sesame and flaxseeds, which contain up to 1 % lignans (500-1,000 mg/100 g) [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the uncertainly concerning the health benefits of flaxseed lignans stems from the indeterminate amount of lignan administered in clinical trials when flaxseed products such as whole flaxseed or defatted flaxseed meal are used as the lignan source (Bloedon et al, 2008;Cornish et al, 2009;Demark-Wahnefried et al, 2008;Hallund et al 2008;Lucas et al, 2002;Pan et al, 2007;Zhang et al, 2008). Recently, standardized flaxseed products have become available for commercial sale and use.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007 "Public Library of Science One" found that type 2 diabetics who consumed flax seed-derived lignin supplements for 12 weeks had lower average blood sugar levels as determined by the A1C test, a measurement of blood glucose control based on the percentage of hemoglobin in the blood that contains glucose molecules. A low score on the Hb A1C test indicates good blood glucose control over the past two to three months, while a high score indicates poor blood glucose control (Pan et al, 2007).…”
Section: Flaxseed Oil For Type 2 Diabeticsmentioning
confidence: 99%